A MoSe2/WSe2 Heterojunction‐Based Photodetector at Telecommunication Wavelengths. (9th October 2018) - Xue, Hui; Wang, Yadong; Dai, Yunyun; Kim, Wonjae; Jussila, Henri; Qi, Mei; Susoma, Jannatul; Ren, Zhaoyu; Dai, Qing; Zhao, Jianlin; Halonen, Kari; Lipsanen, Harri; et al.
Abstract: van der Waals (vdW) heterojunctions enable arbitrary combinations of different layered semiconductors with unique band structures, offering distinctive band engineering for photonic and optoelectronic devices with new functionalities and superior performance. Here, an interlayer photoresponse of a few‐layer MoSe2 /WSe2 vdW heterojunction is reported. With proper electrical gating and bias, the heterojunction exhibits high‐sensitivity photodetection with the operation wavelength extended up to the telecommunication band (i.e. 1550 nm). The photoresponsivity and normalized photocurrent‐to‐dark current ratio reach up to 127 mA W −1 and 1.9 × 10 4 mW −1, respectively. The results not only provide a promising solution to realize high‐performance vdW telecommunication band photodetectors, but also pave the way for using sub‐bandgap engineering of two‐dimensional layered materials for photonic and optoelectronic applications. Abstract : van der Waals heterostructures are demonstrated as building blocks for photonics and optoelectronics . Herein, a sub‐bandgap photodetection at λ = 1550 nm based on a MoSe2 /WSe2 heterojunction is demonstrated. The high responsivity as well as high normalized photocurrent‐to‐dark current ratio indicate that the heterojunction device has promising applications in future optoelectronic.